Tipe tubuh (somatotype) dengan sindrom metabolik pada wanita dewasa non-obesitas usia 25 – 40 tahun - Betsi Kusumaningnastiti; Enny Probosari; Fillah Fithra Dieny; Deny Yudi Fitranti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Body type (somatotype) with metabolic syndrome among non-obese woman aged 25-40 years oldBackground: The prevalence of central obesity was found high in women, not only in obese individuals but also occur in non-obese individuals or metabolically obese normal weight (MONW). Endomorph marked by higher fat mass, which will lead to metabolic disorders.Objective: This study aimed to describe the correlation of somatotype with metabolic syndrome in a non-obese woman.Methods: Cross-sectional observational study, subjects were selected using purposive sampling involving 46 women 25-40 years old with BMI 18.5-24.9 kg/m2 in several offices in the City of Semarang, consist of Balai Besar Teknologi Pencegahan dan Pencemaran Industri, Dinas Pekerjaan Umum, and Dinas Perindustrian dan Perdagangan Central Java. Somatotype data is measured in three components, namely endomorph, mesomorph, and ectomorph. The resulting value of each component is calculated using the Heath-Carter formula. Triglycerides, HDL, and fasting blood glucose measured by enzymatic colorimetric methods. Blood pressure measured by aneroid sphygmomanometer. Syndrome metabolic was defined as metabolic syndrome risk score (cMetS). Data were analyzed by Rank Spearman and Pearson.Results: The subject's body type is endomorph as much as 91.3% and ectomorph-endomorph (8.7%). Central obesity (50%), low HDL levels (28%), hypertriglyceridemia (2%), normal GDP levels (100%), hypertension (15%), metabolic syndrome (13%), and metabolic pre-syndromes (47, 8%) found in the subject of this study. There were correlation between endomorph (p=0.005; r=0.4) and ectomorph (p=0.000; r=-0.53) with waist circumference. There was a significant correlation between endomorph with metabolic syndrome risk score (p=0.05; r=0.129).Conclusions: Endomorph was associated with a metabolic syndrome risk score. Higher endomorph tends to have higher metabolic syndrome risk scores.